2020
DOI: 10.1007/s11663-020-02029-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitriding Potential KN on the Formation and Growth of a “White Layer” on Iron Aluminide Alloy

Abstract: This paper investigates the effect of nitriding potential under well-defined gas nitriding conditions on the formation and growth of a compound layer called “white layer” on a FeAl40 (with the composition of 40 at. pct Al) iron aluminide alloy. The nitriding potential was systematically varied in the range of 0.1 to 1.75 bar−1/2 at 590 °C for 5 hour nitriding time with an ammonia-hydrogen-nitrogen atmosphere. Characterization of the microstructure and phases formed within the white layer was performed using op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…The growth of such surface nitrides is known from nitriding of white-solidified cast irons [12,17] and other alloys. [62][63][64] It is likely driven by stress relief [65,66] and requires outward diffusion of Fe atoms. As the surface nitrides do not form a dense layer, the nitriding atmosphere should have always been in contact with the original samples' surface.…”
Section: Overview Of the Compound Layer Inmentioning
confidence: 99%
“…The growth of such surface nitrides is known from nitriding of white-solidified cast irons [12,17] and other alloys. [62][63][64] It is likely driven by stress relief [65,66] and requires outward diffusion of Fe atoms. As the surface nitrides do not form a dense layer, the nitriding atmosphere should have always been in contact with the original samples' surface.…”
Section: Overview Of the Compound Layer Inmentioning
confidence: 99%
“…An increase in parameters such as temperature and time directly affects the thickness of the nitration layer, and the thermal conductivity decreases by increasing the thickness of the nitride layer. In addition, the thermal diffusion value, defined as the amount of heat energy spread per unit of time, also decreased with the increase of nitride layer thickness [ 70 , 71 ]. Therefore, following the opinion given in the work [ 72 ], it can be concluded that the nitrided layer significantly increases the thermal stability of the coatings sublayers and prevents hardness decrease, as shown in Table 4 and Table 5 , and affects resistance to abrasion and plastic deformation at 700 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of such surface nitrides is related to stress release [58,59] and known from nitriding of white-solidified cast irons [19,60] and Fe-Al alloys. [61][62][63] The coverage of the surface with surface nitrides varies among different a-Fe grains, however, they do not form a dense surface layer even upon nitriding for 48 hours. 3.…”
Section: Identification and Crystallographic Features Of The Nitride Plates-plate-type C¢mentioning
confidence: 99%